Developing a Sustainable Tourism Promotion Strategy for Cultural Events on Sibandang Island - Andriani, Nukeu Novia; Sihombing, Bernadet; Br Sembiring, Cecilia Stevani (Journal of Event, Travel and Tour Management, 2025)
Sibandang Island is part of the Toba Caldera UNESCO Global Sibandang Island, part of the Toba Caldera UNESCO Global Geopark, possesses significant cultural and natural potential, yet faces substantial challenges in tourism promotion. Previous research indicated that marketing feasibility was only 8%, despite cultural and natural potential reaching 98%. This disparity highlights the absence of a targeted and sustainable promotional strategy. This study aims to design a sustainable tourism promotion strategy for cultural events on Sibandang Island, emphasizing local cultural authenticity and sustainability, with a focus on cultural and technological pillars. The methodology employed is qualitative descriptive research. Data analysis utilizes content and thematic analysis based on indicators from a sustainable promotion matrix. Subsequently, the analysis results are developed into a promotional strategy using the SOAR (Strengths, Opportunities, Aspirations, Results) approach. The targeted output is a local culture-based sustainable tourism promotion strategy in the form of a final document, intended as a reference for local government, tourism awareness groups (Pokdarwis), and tourism promotion stakeholders. This research is expected to enhance the effectiveness of tourism promotion and contribute to the sustainable preservation of local culture on Sibandang Island.